Multifunctional che, cleft sentences and presentational c’è in corpora of spoken Italian - Giampieri, Patrizia (Research in Language, 2025)
This paper is aimed at exploring some traits of neo-standard Italian in four different spoken corpora, such as children’s conversations, adult conversations, parliamentary debates, and film subtitles. The following features are investigated: multifunctional che, cleft sentences, and presentational c’è. Building on scholarly examples and sample phrases containing the traits above mentioned, this paper discusses how to search for, retrieve and analyse neo-standard phrasemes in the four corpora. Other features are also presented and investigated on a case-by-case basis. In addition, relative frequencies of phraseme occurrences are noticed and discussed. In this way, a qualitative and a small-scale quantitative comparative approach is developed. The paper findings report that all the traits appear in the corpora with some notable genre-related differences.